2017
DOI: 10.3342/kjorl-hns.2016.17279
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Sleep Disordered Breathing and Quality of Life after Adenotonsillectomy in Pediatric Obstructive Sleep Apnea

Abstract: Background and ObjectivesZZPediatric obstructive sleep apnea (OSA) can have an effect on the quality of life (QOL) such as behavior, school performance, emotional distress and daytime function. We aim to verify changes in sleep disordered breathing based on polysomnographic findings and disease specific health related QOL before and after adenotonsillectomy in Korean children with OSA. Subjects and MethodZZA total 20 children aged 3 through 13 years old (mean age=6.7 years old and male/female=14/6) with OSA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Results of PSG and KOSA-18 survey in children with OSA have revealed significant improvements in OSA and related QOL after adenotonsillectomy. 25 Based on the analysis of 37 articles on quantitative assessment of QOL in pediatric sleep apnea syndrome, a systematic review by Todd et al demonstrated that QOL improved in the shortterm follow-up, with a strong indication of improvement in long-term follow-up after adenotonsillectomy. 18 Mitchell et al administered the OSA-18 to 34 children with OSA before and at 9 and 24 months after adenotonsillectomy and reported significant improvements in QOL, which were prominent in the short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of PSG and KOSA-18 survey in children with OSA have revealed significant improvements in OSA and related QOL after adenotonsillectomy. 25 Based on the analysis of 37 articles on quantitative assessment of QOL in pediatric sleep apnea syndrome, a systematic review by Todd et al demonstrated that QOL improved in the shortterm follow-up, with a strong indication of improvement in long-term follow-up after adenotonsillectomy. 18 Mitchell et al administered the OSA-18 to 34 children with OSA before and at 9 and 24 months after adenotonsillectomy and reported significant improvements in QOL, which were prominent in the short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Results of PSG and KOSA‐18 survey in children with OSA have revealed significant improvements in OSA and related QOL after adenotonsillectomy . Based on the analysis of 37 articles on quantitative assessment of QOL in pediatric sleep apnea syndrome, a systematic review by Todd et al demonstrated that QOL improved in the short‐term follow‐up, with a strong indication of improvement in long‐term follow‐up after adenotonsillectomy .…”
Section: Discussionmentioning
confidence: 99%